Registration of 'Silver River' Sweetclover. Issue 2 (27th April 2017) - Smith, G. R.; Evers, G. W.; Ocumpaugh, W. R.; Forbes, T. D. A.; Ong, K.; Foster Malone, J.
Abstract : 'Silver River' (Reg. No. CV‐6, PI 678795) is a rust‐resistant cultivar of white‐flowered, annual sweetclover ( Melilotus albus Medik.) adapted to southern and central Texas. Sweetclover rust ( Uromyces striatus Schroet.) causes a range of plant disease symptoms, including leaf drop, reduced seed and forage yield, and premature plant death. The breeding and evaluation of Silver River for rust resistance was conducted at Beeville, TX, under severe epiphytotics of sweetclover rust. Two cycles of mass selection at Beeville were used to improve the rust resistance of a sweetclover PI line from Uruguay. The original PI population had 21% rust‐resistant plants. Silver River averaged 91% resistant plants at Beeville in 2014 and 2015, compared with 'Hubam', which had a 2‐yr average of 7% resistance. Silver River is similar to Hubam in forage yield and maturity. This new cultivar will improve the reliability of annual sweetclover in cattle grazing systems and wildlife supplemental forage plantings in southern and central Texas.